The Role of Spiritual Beliefs and Practices in Sustainable Livelihoods: A Case Study of Muga Silkworm Rearing in Assam - Baruah, Tulika (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
In Assam, the Muga silk industry is more than a source of economic enhancement, it is a living tradition interwoven with reverence for nature. For generations, Muga rearers have practiced their craft not merely as a livelihood, but as a sacred responsibility guided by spiritual beliefs and rituals that honor the silkworm and the host plants. This study aims to bring the spiritual traditions practiced generation after generation playing a vital role in enhancement of Muga production and preservation of environment This case study examines the spiritual beliefs, rituals and ethical imperatives through in-depth interviews with prominent Muga rearers in Dhakuakhana subdivision, Lakhimpur district, Assam and advocates for their ethical integration with modern scientific interventions to enhance productivity and preserving cultural integrity. Findings underscore the potentiality of these practices to counter modern threats like pesticide use in the nearby rearing areas, use of plastic items instead of traditional tools etc.